(untitled) (Research, Society and Development, 2022)
Pelvic Inflammatory Disease (PID) is the acute inflammation of the female upper genital tract, which can be triggered by recurrent vaginal candidiasis, which is one of the causes of its development, presenting frequently in a woman’s life. OBJECTIVE: To evaluate the approach to the etiological aspects and the pharmacological treatment of acute pelvic diseases, emphasizing recurrent candida. This is a methodical literature review, with the proposal to carry out a search of scientific articles through electronic research, based on the data listed: Google Scholar, SCIELO (Online Scientific Electronic Library) and VHL (Virtual Health Library), PUBMED, between the years 2010 to 2022. Pelvic inflammatory disease is affected by STD’s, and a sexually active life with multiple unprotected partners can be claimed as a risk factor. Candidiasis triggering PID, having a correct treatment such as changing eating habits that help to prevent unwanted Candida and consequently a non-development of PID.